Behavioral theory in sociology: essays in honor of George C. Homans - Hamblin, Robert L.; Homans, George Caspar; Kunkel, John H. (Transaction Books)
Skinner, B. F. George C. Homans at Harvard.--Gibbs, J. P. Homans and the methodology of theory construction.--Johnson, W. T. Exchange in perspective.--Gergen, K. J. Social exchange theory in a world of transient fact.--Stolte, J. F. and Emerson, R. M. Structural inequality.--Burgess, R. L. and Nielsen, J. M. Distributive justice and the balance of power.--Schmitt, D. R. and Marwell, G. Cooperation and the human group.--Kozloff, M. A. Social exchange and behavioral change in families of deviant children.--McAuliffe, W. A. and Gordon, R. A. A test of Lindesmith's theory of addiction.--Leik, R. K. and Leik, S. A. Transition to interpersonal commitment.--Parsons, H. M. What happened at Hawthorne?--Hamblin, R. L. and Crosbie, P. V. Anomie and deviance.--Kimberly, J. C. Inconsistency among components of stratification and cognitive consistency and reward-cost processes.--Hamblin, R. L. and Miller, J. L. L. Reinforcement and the origin, rate, and extent of cultural diffusion.--Kunkel, J. H. The behavioral perspective of social dynamics.--Hamblin, R. L. Behavior and reinforcement.--Conclusion